Changes in the Differentiation Program of Birch Cambial Derivatives following Trunk Girdling - Aleksandra Serkova; Tatiana Tarelkina; Natalia Galibina; Kseniya Nikerova; Yulia Moshchenskaya; Irina Sofronova; Nadezhda Nikolaeva; Diana Ivanova; Ludmila Semenova; Ludmila Novitskaya (Forests, 2022)
The mechanisms regulating the tree trunk radial growth can be studied in original experiments. One technique for studying cambium activity (the meristem involved in radial growth) under conditions of an increased photoassimilate level is trunk girdling. We girdled the trunks of 17- to 22-year-old silver birch plants (Betula pendula Roth var. pendula) during the active growth period and collected xylem and phloem samples at two height levels (1 cm and 35 cm) above girdle, 10, 20, and 30 days after girdling. We investigated the changes that occurred at the anatomical level, as well as the activities of sucrose-metabolizing enzymes and antioxidant-system enzymes and the expression of genes that encode proteins involved in sucrose and auxin transport and metabolism. A moderate increase in photoassimilates (35 cm above the girdle) resulted in a change in the ratio of phloem to xylem increments and an increase in the proportion of parenchyma in the conducting tissues. The increase of photoassimilates above the level at which they can be used in the processes of normal tissue growth and development (1 cm above the girdle) led to xylogenesis suppression and the stimulation of phloem formation, a significant increase in the parenchyma proportion in the conducting tissues, and formation of large sclereid complexes. The differentiation of parenchyma and sclereid cells coincided with biochemical and molecular markers of abnormal conducting tissue formation in Karelian birch, which are also characterized by high proportions of parenchyma and sclereid near the cambium. The results obtained are important in understanding the cambium responses to the photoassimilate distribution changes and estimating tree productivity and survival under changing environmental conditions.